Turkish Education Writing Process: Digital Storytelling - Gökhan Dayan; Pınar Girmen (Anı Publishing, 2018)
The aim of the study is description of digital products created by the students of primary school, 4th grade during Turkish lesson writing process. With the critical state sampling method, which is one of the purposeful sampling types, working group of the study established a primary school where the children of families living in rural areas have been educated. The research was carried out in this primary school in the second semester of 2016-2017 academic year. In the collection of research data; full participant observation, researcher diaries, student diaries and student digital products were used. Analysis of data was done through content analysis in the research. During research process, improvements were encountered considering the aspects of the quality and quantity of elements such as words, sentences and number of scenes in the digital stories created by students. Thanks to creating multiform texts of digital narration studies, it was determined that students produced more regular texts by showing development about paying attention writing and punctuation rules. In Turkish lectures, the control of these variables will be effective when they are carried out in a functional way without going into digital narrative studies.